Drivers of entrepreneurship development in South Asia: empirical insights and policy recommendations - Emon Kalyan Chowdhury (Journal of Innovation and Entrepreneurship)
Abstract Entrepreneurship plays a crucial role in driving economic growth and development, and understanding the factors that shape entrepreneurship is essential. This research paper aims to investigate the factors influencing entrepreneurship development in South Asian countries by analyzing the role of institutional quality, technological innovation, social capital, economic growth, trade openness, and cultural values. The study utilizes panel data from various sources covering the period from 2010 to 2023. Statistical models such as Pedroni panel cointegration test, regression analysis, and the two-step system generalized method of moments are applied for analysis. The major findings of the study reveal that economic growth, institutional quality, financial development, technological innovation, foreign direct investment, social capital, trade openness, and cultural values significantly influence entrepreneurship development in South Asian countries. This study recommends promoting sustainable economic growth, improving access to finance for entrepreneurs, enhancing institutional quality, fostering technological innovation and knowledge transfer, supporting social capital networks, promoting trade diversification, and aligning cultural values with entrepreneurship development to provide a conducive environment for entrepreneurship and facilitate economic growth and development in South Asian countries.